Good Governance Implementation by PERMA 1/2019 in Letter Evidence Submission Regulation For E-Litigation Cases - Gerry, Michael; Rizkiana, Rina Elsa (The Digest: Journal of Jurisprudence and Legisprudence, 2023)
The judiciary, responding to societal demands for sound governance, aligns itself with the 2010–2035 Judicial Reform Blueprint, emphasizing the use of information technology for restructuring. E-Litigation emerges as a significant outcome of Indonesia's judicial reforms, supported by SK KMA RI Number 129/KMA/SK/VIII/2019 and PERMA 1 of 2019 as the legal basis. The implementation of e-Litigation is expected to adhere to the principles of good governance outlined in legal philosophy, particularly concerning the legitimacy of evidence in civil cases during e-Litigation. However, the legislative document, specifically PERMA 1/2019, lacks explicit technological guidelines, posing a challenge to the effective implementation of good governance. This research aims to scrutinize the concept of good governance, the legal foundation for e-Litigation, and the application of responsive, effective, and efficient principles in controlling the admissibility of documentary evidence in e-Litigation within civil cases. Utilizing a statutory method, the study employs a normative approach to law. The findings indicate that the current legal framework for the admissibility of evidence in civil e-Litigation cases hinders the fulfillment of responsive, effective, and efficient e-Litigation principles. Consequently, a modification to the legal framework governing the admissibility of evidence in civil e-Litigation is warranted to align with the principles of good governance.